Peranan Haji Bun Yamin terhadap Pembangunan dan Pendirian Masjid Taqwa Desa Seri Tanjung - Mukhlisin Nata Hudin; Junadhan Syapa Widyaksa; Muhammad Daffa Pratama; Rimadia Rimadia; Maulidya Dwi Melantika; Hudaidah Hudaidah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Mosques have an important role in the lives of Muslims, not only as places of worship, but also as centers of social, cultural, and educational activities. This research reveals the history of the establishment of the Taqwa Mosque in Seri Tanjung Village, Tanjung Batu District, Ogan Ilir Regency, as well as the important role of Manda Haji Bun Yamin as a local figure in the process of building the mosque. Using historical and sociological approaches, this study shows that the mosque not only reflects the spiritual development of the community, but also symbolizes unity and independence in building religious facilities independently. The results found that Manda Haji Bun Yamin had a strong religious and social vision, reflected in his initiative to build a permanent two-story mosque that would later become the center of community activities. The Taqwa Mosque is not only a place of worship, but also plays a role in religious education, distribution of social assistance, preservation of traditions, and strengthening the value of tolerance between religious communities. This research emphasizes the importance of exploring and documenting local history as part of the cultural heritage and identity of the local Muslim community.